Erythroderma: a clinico etiological study of 77 patients in a tertiary care centre in Kerala - Itty, Abin Abraham; Sridharan, Rajiv; Thyvalappil, Anoop; Sudhamani, Bindurani (International Journal of Research in Dermatology, 2020)
Background: Erythroderma is defined as generalized erythema and scaling of the skin affecting more than 90% of body surface area. Identification of the underlying disease process represents one of the most complex challenges in proper patient care. Methods: A retrospective study was done in Department of Dermatology in a Tertiary Care Centre. History, clinical findings and investigations of erythroderma patients were recorded and clinic-histopathological correlation was analyzed by kappa coefficient (К). Results: Erythroderma was more prevalent in elderly males with a mean age of 64.56 years and a male to female ratio of 3:1. A clinical evidence of pre-existing dermatoses was found in 65 patients, commonest being eczema (41.3%) followed by psoriasis (40.3%). Evidence of a trigger was seen in 54.54% patients, commonest being the use of ayurvedic medications (42.8%). Clinico-histopathological correlation was seen in 53.9% cases. Conclusions: Although the clinical presentation of erythroderma is similar, etiological factors are varied and it depends largely on the population studied. Most commonly, erythroderma is due to generalization of pre-existing dermatoses as seen in our study. Hence careful evaluation of clinical clues and histopathological correlation plays a pivotal role in diagnosis of the primary cause and the effective management of erythroderma.